A systematic literature review of university technology transfer from a quadruple helix perspective: toward a research agenda. (25th July 2016) - Miller, Kristel; McAdam, Rodney; McAdam, Maura
Abstract : Within recent years, there has been a rapid expansion of the University's role in economic development. This has resulted in University Technology Transfer (UTT) taking place within an increasingly complex network of regional stakeholders. This complexity has resulted in quadruple helix models where the triple helix model of academia, industry and regional government now includes societal based innovation users as a fourth helix. Despite this development, extant research is fragmented and lacks coherent frameworks and conceptualisations which fully depict the dynamic and evolving nature of UTT. Accordingly, this article reviews Mode 2 UTT from a quadruple helix perspective to identify key themes to develop a research agenda which reflects progression from a triple into a quadruple helix ecosystem.